The Growth Spiral Money, Energy, and Imagination in the Dynamics of the Market Process - Binswanger, Hans Christoph; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
This book develops a new theory of the modern economy. Conventional economic theory is (still) based on an essentially static notion of equilibrium. In contrast, this book offers an analysis of the economic process based on a truly dynamic approach. It understands modern economic activity as manifesting itself in a growth spiral. There are two main drivers of the dynamics of this spiral: steady money creation in the banking system, on the one hand; and the continuous inflow of energy and raw materials through the exploitation of natural resources, on the other. Both driving forces are generally neglected by the conventional theory. Understanding their role is absolutely essential for preventing our economy from being more and more exposed to financial and ecological crises. This book offers important insights about the functioning of the modern economy and addresses the specialist as well as the interested lay reader.
Preface to the German Edition -- Preface to the English Edition -- Introduction -- Part I: Money and the Market -- Part II: Market and Production -- Part III: Money and Production in the Dynamics of the Growth Spiral - Growth Imperative and Growth Impetus -- Summary and Outlook -- References.
Keywords: Economics; Environmental law; Endogenous growth (Economics).; Economics/Management Science; Economic Growth; Economic Theory; Environmental Law/Policy/Ecojustice.